Multidisciplinary analysis including neotectonic mapping, morphotectonic indices, applied geophysics and remote sensing techniques for studying recently recognized active faults in Northwestern Peloponnese (Greece) - Mavroulis, S.; Dilalos, S.; Alexopoulos, J.; Vassilakis, Emm.; Lekkas, E. (10 years after the 2008 Movri Mt M6.5 Earthquake; An earthquake increasing our knowledge for the deformation in a foreland area, 2018)
A multidisciplinary analysis comprising neotectonic mapping, morphotectonic indices, applied geophysics and remote sensing techniques was applied in the area affected by the 2008 NW Peloponnese (Western Greece) in order to map the recently-recognized E-W striking Pineios River normal fault zone with a high degree of accuracy, and to better understand its contribution to the evolution of the ancient region of Elis during Holocene time. Quantitative constraints on deformation caused by the faulting were applied through the application of morphometric and morphotectonic indices including drainage network asymmetry, longitudinal river profiles and valley floor slope changes, the river sinuosity index (SI) of modern channels as well as mountain front indices including mountain front sinuosity (Smf) and percentage of faceting along mountain front (F%). All of the aforementioned indicated that the Pineios fault zone is a highly active structure. The study area consists mainly of a succession of Pliocene to Holocene sediments. Already published 230Th/238U dating of corals from the upper layers of the sequence indicates a Tyrrhenian age for samples spanning three complete sections from the footwall of the Pineios fault zone. The deposition ages were determined to be 103 ka for the Psari section (at an elevation of 40-45 m above a.s.l.), 118 ka for the Neapolis section (at an elevation of 60–65 m a.s.l.) and 209 ka for the Aletreika section (at an elevation of 140–145 m a.s.l.). The sampling sites that are located north of Pineios fault zone should be located on a single fault block because there is no sign of tectonic disruption between them. The ages of these dated samples correspond to oxygen isotope stages 5.3, 5.5 and 7.3. These stages represent high sea-level stands for the Mediterranean Sea and especially for the western coast of Peloponnese. In particular, at 103 ka sea-level was ~13 m below present sea-level, at 118 ka it was ~1 m below present sea-level and at 209 ka it was ~7 m below present sea-level. From the age of each sample and the sea-level change that has occurred since deposition, uplift rates for the footwall of the Pineios fault zone were calculated as ~0.26 mm/yr for the Psari area, ~0.50 mm/yr for the Neapoli area and ~0.64 mm/yr for the Aletreika area. The maximum uplift rate of 0.64 mm/yr occurs in close proximity to the fault zone. The areas with lower uplift rates are located much further to the north. Because all sample locations are inferred to be within the same fault block, this implies back tilting of the fault block toward north, in full agreement with the rotational block-faulting inferred from structural studies based on fieldwork in the surrounding area.